Conflitos de atividades antrópicas com a conservação das tartarugas marinhas na região da Bacia Potiguar, Brasil - Ventura, Aline da Costa Bomfim (2022)
Brazil has a coast that is threatened by economic activities and accelerated urbanization process, causing ecosystem unbalance and decreasing socioenvironmental quality. The existing socioeconomic activities in the Potiguar Basin, Northeastern Brazil, pose risks to the sea turtle species that occur in the region. We analyzed gonad samples and data obtained of strandings and nests of sea turtles from 2010 to 2021 during the activities Beach Monitoring Project in Potiguar Basin to assess the potential impacts of human activities on sea turtles, as well as the nesting ecology and reproductive maturation of these animals. Anthropogenic interaction was classified into 12 categories (eight related to fishing activities). We analyzed 6,007 strandings, including four sea turtle species (Chelonia mydas, Green turtle; Eretmochelys imbricata, Hawksbill turtle; Lepidochelys olivacea, Ridley turtle; Caretta caretta, Loggerhead turtle) and anthropogenic interaction was observed in 12.88% (n=774) of the strandings. Chelonia mydas represented 94.05% of the total records with anthropogenic interaction and fishing-related strandings accounted for 81.65%. Juvenile individuals were more affected than adults; likewise, females were more affected than males. Icapuí and Areia Branca are very populous municipalities, and showed large number of strandings with signs of anthropogenic interaction. Our analyses revealed that fishing-related strandings were reported throughout the year; however, a larger number of records occurred in the dry season and during the lobster-fishing season. The municipalities of Macau/RN and Guamaré/RN were the priority areas for reproduction of sea turtles, with the highest number of registered nests (60.70% and 20.82%, respectively). The nesting season for E. imbricata occurred between December and May and for L. olivacea from March to August. Hawksbills had clutch size, incubation time, number of unhatched eggs, and dead hatchlings higher than olive Ridley turtles; nevertheless, they presented lower hatching success. Precipitation between 0 and 22 mm and relative humidity (RH) higher than 69% increased the hatching success rate for E. imbricata; however, rainfall above 11 mm and RH 64% had the same effect for L. olivacea. There is anthropogenic influence on the levels of reproductive posture of females and on the hatchlings and nests of these animals; buildings, light pollution, fishing activity, egg theft and anthropogenic waste were the main impact indicators found in the area. The length of the carapace of sea turtles is not appropriate to identify the stage of reproductive maturation when used in isolation, and histological analysis is an adequate technique for this purpose, therefore, it is recommended to adopt the minimum size in which reproductive activity is observed in the gonadal tissue, through histological analysis, as a basis for the initial reproductive size. In addition, the histomorphometric analysis offers opportunities to increase the understanding of the attributes that influence the sexual maturation of these animals. The results of this research provide subsidies for management measures, mitigation, and the adoption of public policies to minimize the impacts on sea turtles, helping to conserve them.